Economics and management of geotourism - Braga, Vitor; Duarte, António; Marques, Carla Susana (Tourism, hospitality & event management, 2022)
This book covers all aspects of the economics and management of geotourism, an increasingly important sector of nature tourism that focuses on the geology and landscape of different territories, providing a pleasurable and educational tourist experience. Geotourism is a sustainable form of tourism that has the potential to deliver significant benefits to host communities. To date, however, geotourism has been examined primarily from the natural sciences perspective, to the detriment of issues related to local social and economic impacts, inter-organizational collaboration, tourist responses, and community participation. This book therefore fills a major gap in the literature. While a key focus is the impacts of geotourism on economic and social development processes and the quality of life of local populations, detailed attention is also devoted to topics such as geopark and geosystem management, innovative and entrepreneurial strategies in geotourism, and territorial marketing. In addition, readers will gain a clear understanding of the extent to which the opportunities and challenges facing geotourism reflect current trends in the tourist industry as a whole